Transcendental Approach into Danarto’s Selected Short Stories - ., Baihaqi; ., Imran; Yakob, Muhammad (KnE Social Sciences, 2018)
This study aimed to analyze the transcendental approach depicted in selected short stories written by Danarto. This approach seeks to show how far the transcendental approach has colored the anthology of short stories written by Danarto (1992) and how that approach described through his works. Generally, the resulting works relies on tasawuf kejawen obtained through spiritual, religious, mystic, mystical, and divine experience into themes in each of his works. There are five short stories that made the object of research were anthology of godlob, anthology of Adam Ma’rifat, anthology of Berhala, anthology of Gergasi and anthology of Setangkai Melati di Sayap Jibril. The method used in this study is descriptive qualitative through content analysis techniques refers to Fraenkel and Wallen (2012) stating that content analysis is a technique used to assess human behavior indirectly in some short stories written by Danarto. The results of this study showed that the transcendental approach was seen in the short stories produced by Danarto through characters, symbols, the absurdity of the story, the meaning of the story itself, the formation of a separate world not limited by the author’s space, time and events and personal experiences. This showed that the author in producing his works tends to position himself as a creature of Allah Almighty and his unification with Allah Almighty becomes the highest point in his fusion with the Creator of Universe. Keywords: trancendental, Short Stories, Creator of Universe